Mycorrhizae are symbiotic structure developed by the roots of plants and fungal mycelia. These mycorrhizae are often necessary for the growth of forest trees. This study was undertaken to determine the effect of the application of nitrogen and phosporus on the development of mycorrhizae in pinus merkusii. Andosol, collected in puncak, and latosol, collected in Darmaga, were used in this experiment. A seedling, transplanted into a pot containing 490 gr of dried soil, served as an experimental uni - Chairil Anwar; Soetrisno Hadi; Sukandar Djokosuhardjo (Buletin Hama dan Penyakit Tumbuhan, 1979)
Mycorrhizae are symbiotic structure developed by the roots of plants and fungal mycelia. These mycorrhizae are often necessary for the growth of forest trees. This study was undertaken to determine the effect of the application of nitrogen and phosporus on the development of mycorrhizae in pinus merkusii. Andosol, collected in puncak, and latosol, collected in Darmaga, were used in this experiment. A seedling, transplanted into a pot containing 490 gr of dried soil, served as an experimental unit. Nitrogen ((NH4)2SO4) was applied at o ppm, 60 ppm, 120 ppm,